ASI-RIM neuronal axis regulates systemic mitochondrial stress response via TGF-β signaling cascade - Zihao Wang; Qian Zhang; Yayun Jiang; Jun Zhou; Ye Tian (Nature Communications)
Abstract Morphogens play a critical role in coordinating stress adaptation and aging across tissues, yet their involvement in neuronal mitochondrial stress responses and systemic effects remains unclear. In this study, we reveal that the transforming growth factor beta (TGF-β) DAF-7 is pivotal in mediating the intestinal mitochondrial unfolded protein response (UPRmt) in Caenorhabditis elegans under neuronal mitochondrial stress. Two ASI sensory neurons produce DAF-7, which targets DAF-1/TGF-β receptors on RIM interneurons to orchestrate a systemic UPRmt response. Remarkably, inducing mitochondrial stress specifically in ASI neurons activates intestinal UPRmt, extends lifespan, enhances pathogen resistance, and reduces both brood size and body fat levels. Furthermore, dopamine positively regulates this UPRmt activation, while GABA acts as a systemic suppressor. This study uncovers the intricate mechanisms of systemic mitochondrial stress regulation, emphasizing the vital role of TGF-β in metabolic adaptations that are crucial for organismal fitness and aging during neuronal mitochondrial stress.